Bank disintermediation: South Africa - Chetty, Kubandran (My University, 2012)
The conventional theory of financial intermediation suggests that banks are the main conduit between savers and borrowers however, research has shown that international banks are losing importance in intermediating i.e. mobilise savings and allocating these funds among competing borrowers - this international reality is due to a number of reasons including changes in regulation, growth in capital markets, non-bank financial intermediaries, foreign competition etc. South Africa has a highly concentrated banking sector with the five largest banks holding more than 90% of the industry’s assets however growth in non-bank financial intermediaries are threatening the intermediary role and profitability of banks - this research serves to investigate whether bank disintermediation is occurring in the South African context and whether the traditional role of banks is declining.
Keywords: Finance; Intermediation; Bank loans; South Africa